Tahap Perlaksanaan Maqasid Syariah dalam Pembangunan Produk Sukuk di Malaysia: Satu Kajian Kualitatif - Muhammad Azizur Rahman, Ramli; Mansor, Sulaiman (Universiti Malaysia Pahang, 2017)
The Islamic capital market was established to keep the benefits and goods of the market participants. Sukuk is Islamic investment certificate that funds large-scale projects. In Malaysia, by 2016 the sukuk market size stood at RM 661.08 bilion which accounted for almost 56.36% of the Malaysia capital market. The large amount of sukuk issuance in Malaysia leads to Maqasid Shariah issues. Among the issues of sharia is the controversy of criticisms of sukuk non-compliant sukuk and it is merely a feek trick that justifies conventional concepts in it. Therefore it needs to be measured and analyzed based on the concept of true Maqasid Shariah so that it can solve this phenomenon. The study was conducted based on qualitative methodology using the interview method and analyzing it using case study analysis. The analysis is done with NVivo software. The finding found there is 5 themes which are factors to determine the level of Maqasid Shariah in the development of sukuk products in Malaysia. In conclusion, development of the sukuk structure in Malaysia meets the concept of Maqasid Shariah. However, the level of Maqasid Shariah awareness needs to be enhanced and it can be categorize as a maslahah-based sukuk classification. With this new categories, all of sukuk players can develop sukuk through the Maqasid Shariah concept.